Transcriptomic approach for understanding the adaptation of salmonella enterica to contaminated produce - Park, Sojung; Nam, Eun woo; Kim, Yeeun; Lee, Seohyeon; Kim, Seul I.; Yoon, Hyunjin (Journal of Microbiology and Biotechnology, 2020)
Salmonellosis is a form of gastroenteritis caused by Salmonella infection. The main transmission route of salmonellosis has been identified as poorly cooked meat and poultry products contaminated with Salmonella. However, in recent years, the number of outbreaks attributed to contaminated raw produce has increased dramatically. To understand how Salmonella adapts to produce, transcriptomic analysis was conducted on Salmonella enterica serovar Virchow exposed to fresh-cut radish greens. Considering the different Salmonella lifestyles in contact with fresh produce, such as motile and sessile lifestyles, total RNA was extracted from planktonic and epiphytic cells separately. Transcriptomic analysis of S. Virchow cells revealed different transcription profiles between lifestyles. During bacterial adaptation to fresh-cut radish greens, planktonic cells were likely to shift toward anaerobic metabolism, exploiting nitrate as an electron acceptor of anaerobic respiration, and utilizing cobalamin as a cofactor for coupled metabolic pathways. Meanwhile, Salmonella cells adhering to plant surfaces showed coordinated upregulation in genes associated with translation and ribosomal biogenesis, indicating dramatic cellular reprogramming in response to environmental changes. In accordance with the extensive translational response, epiphytic cells showed an increase in the transcription of genes that are important for bacterial motility, nucleotide transporter/metabolism, cell envelope biogenesis, and defense mechanisms. Intriguingly, Salmonella pathogenicity island (SPI)-1 and SPI-2 displayed up- and downregulation, respectively, regardless of lifestyles in contact with the radish greens, suggesting altered Salmonella virulence during adaptation to plant environments. This study provides molecular insights into Salmonella adaptation to plants as an alternative environmental reservoir.
Keywords: Bacterial Proteins; Food Contamination; Gene Expression Profiling; Gene Expression Regulation, Bacterial; Genomic Islands; Life Style; Raphanus; Salmonella enterica; Salmonella Infections; Sequence Analysis, RNA; Transcriptome; Virulence; Epiphytic; Planktonic; Produce; Salmonella enterica; Transcriptomics